Water supply system repair works / Muhammad 'Ainul Furqon Syarif - Syarif, Muhammad 'Ainul Furqon (Universiti Teknologi MARA, Perak, 2022)
Water supply system is important to elaborate and this report will be mainly discuss about the construction and repair works of Water Supply System based on my company,Global Etika Jaya Sdn Bhd Report and Files.This tender project name is Kerja-Kerja Pembaikan Sistem Bekalan Air di Sekolah Menengah Kebangsaan Za’aba, Kuala Pilah, Negeri Sembilan Darul Khusus.This report objective to explain the method of waterproofing for water tank.Therefore,the important objectives of this report is to explain the importance of doing soil investigation and benefits using Probe Mackintosh Test that applied for water tank construction and also to explain in detail the procedure of MLT Test because this project will build a 7 levels of water tank tower with 70 000 GALLON of MALSTORE MAIN WATER TANK.